Some Observations on Santa Maria in Campo Marzio - David H. Bell (Oz, 1984)
In the 17th century Francesco Borromini (1599-1667) revolutionized architectural design. Among the most notable of his achievements were his unprecedented attitudes toward the plastic aspects of architectural form…